Efektivitas dan Efisiensi Penggunaan Knapsack Sprayer dan Knapsack Motor Pada Penyemprotan Gulma di Perkebunan Kelapa Sawit - Yuliyanto .; Nafrin Wijaya Kesuma; Rufinusta Sinuraya (JURNAL CITRA WIDYA EDUKASI, 2017)
Spraying activities is a important aspect of the maintenance activities of palm oil. Use proper spray equipment capable of reducing the cost of weed control in palm oil plantations. Spraying is usually done with a knapsack sprayer (solo) with weeds mortality conditions are uneven so that the necessary tools other spraying with spraying conditions are equitable and more cost-effective, such as the motor knapsack sprayer. This study aims to determine the effectiveness and efficiency of spraying equipment knapsack sprayer (solo) and a motor knapsack sprayer in oil palm plantations. The research was conducted at PT Agro Muko Air Bikuk Estate, Mukomuko, Bengkulu Province. The method used is observation, data collection and information through interviews. Based on the results of the study, the mortality rate of weeds in a knapsack sprayer (solo) less evenly distributed, only 90%, whereas for the motor knapsack sprayer up to 99%. The total cost of spraying using a knapsack sprayer (solo) is Rp 34,610/ha, while the total cost of spraying using a knapsack sprayer motorcycle is Rp 27,241/ha, so that there is a difference in cost of spraying Rp 7,369/ha. The use of a motor knapsack sprayer spraying tool, enables the spraying activity and reduce the cost of application.